The use of peroxide value as a measure of quality for walnut flour stored at five different temperatures using three different types of packaging - Vanhanen, L.P.; Savage, G.P.; Mathooko, F. M (Orgz, 2018)
Walnut flour, a by-product from the production of cold-pressed walnut oil, can contain up to 20% oil, which contains high levels of polyunsaturated fatty acids and is, therefore, potentially unstable. In this experiment, ground walnut flour was stored in three types of container, polypropylene plastic containers, multi-walled plastic-lined paper bags and manila (brown) paper bags. These containers were stored at mean temperatures of 24.6, 3.3, 10.4, 14.3 and 23.0 C for 26 weeks. The moisture content and the peroxide value of the oil extracted from the flour were determined every four weeks for 26 weeks. The initial peroxide value of the freshly ground flour was 0.01 ± 0.008 meq O2/kg oil. After 26 weeks of storage, all samples had an increased peroxide values when compared to the values for oil extracted from the freshly extracted walnut flour. After 26 weeks storage the mean peroxide levels of all treatments were below 1.0 meq O2/kg oil, i.e., lower than that found in commercial samples of walnut oil. Overall, it is recommended that walnut flour should be stored below 23 C with careful consideration given to the moisture content of the storage atmosphere and the type of package used to store the walnut flour
Keywords: Walnut flour; Storage; Packaging; Moisture content; Peroxide value